Application of MRI and Biomedical Engineering in Speech Production Study - Ventura, Sandra Moreira Rua (2021)
Speech production has always been a subject of interest both at the morphological and acoustic levels. This knowledge is useful for a better understanding of all the involved mechanisms and for the construction of articulatory models. Magnetic resonance imaging (MRI) is a powerful technique that allows the study of the whole vocal tract, with good soft tissue contrast and resolution, and permits the calculation of area functions towards a better understanding of this mechanism. Thus, our aim is to demonstrate the value and application of MRI in speech production study and its relationship with engineering, namely with biomedical engineering. After vocal tract contours extraction, data were processed for 3D reconstruction culminating in model construction of some of the sounds of European Portuguese. MRI provides useful morphological data about the position and shape of the different speech articulators, and the biomedical engineering computational tools for its analysis.